A Preparative Approach of TiO2-ZrO2 Coating Using Aquo-Based TiO2 Precursor Useful for Light Reflective Application. Issue 4 (2nd October 2021) - Bhattacharyya, Suparna; Medda, Samar Kumar; Naskar, Milan Kanti
Abstract : TiO2 -ZrO2 composite coating was prepared onto glass substrate via sol-gel dip-coating technique using aquo-based titanium(IV) oxysulphate (TOS) and zirconium(IV) n-propoxide (ZP) as the precursor sources of TiO2 and ZrO2, respectively followed by calcination at 500 o C/1 h. The samples were characterized by FTIR, Raman, UV/visible/ NIR, GIXRD, FESEM, TEM and XPS studies. The thickness and RI of the coating were measured ellipsometrically. The coated glasses with coating thicknesses of 110±10 nm having refractive index of 1.95±0.05 were found to be uniform with good hardness (≥3H) and adhesion properties. The bonding nature of Ti-O and Zr-O was confirmed by FTIR and XPS analyses while Raman and GIXRD studies revealed the crystalline nature of TiO2 -ZrO2 composite. FESEM and TEM images revealed crack-free and spider web-like nature of the deposited coating, respectively. The coated TiO2 -ZrO2 composite showed >20% of average reflection within wavelength range of 350-2500 nm. The above nanocomposite based coated glass could be used as heat reflecting window for efficient energy saving building components. GRAPHICAL ABSTRACT: UF0001